Chapter San Miniato al Monte e lo spazio politico fiorentino nel XIII secolo - Faini, Enrico (Fragmentaria. Studi di storia culturale e antropologia religiosa, 2021)
Starting from the example of San Miniato al Monte, the essay dwells on the relationship existing between Florentine aristocracy and religious institutions. These were indispensable elements for the occupation of the urban 'political space', thanks to the social networks they controlled. Their political role - until now poorly investigated - was clearly recognised by the new ruling groups (Popolo). For this reason, the Florentine Popolo's regime at the end of the thirteenth century tried to break the connection between aristocratic families and religious institutions, also through the use of precise rules that had become part of the Ordinamenti di Giustizia.